Rendezvous Data Collection Using a Mobile Element in Heterogeneous Sensor Networks - Junzhao Du; Hui Liu; Longfei Shangguan; Luo Mai; Kai Wang; Shucong Li (International Journal of Distributed Sensor Networks)
We study the rendezvous data collection problem for the Mobile Element (ME) in heterogeneous sensor networks where data generation rates of sensors are distinct. The link quality is instable in our network model and the sensory data cannot be aggregated when transmitting. The Mobile Element is able to efficiently collect network wide data within a given delay bound; meanwhile the network eliminates the energy bottleneck to prolong its lifetime. For case study, we consider the trajectory planning for both Mobile Relay and Mobile Sink on a tree-shaped network. In the Mobile Relay case where the ME's trajectory must pass through a sink to upload sensory data for further processing, an O ( n lg n ) algorithm named RP-MR is proposed to approach (1) the optimal Rendezvous Points (RPs) to collect global sensory data; (2) the optimal data collection trajectory for the Mobile Relay to gather the cached data from RPs. In the Mobile Sink case where the Mobile Element can process the sensory on its motion, we develop an O ( n lg 2 n ) algorithm named RP-MS to recursively investigate the optimal solution. Both the theoretical analysis and extensive simulations verify the correctness and effectiveness of proposals.